BEBERAPA FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Ningsih, Endang Kusdiah; Johan, Bahdar (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2017)
Efforts to increase state revenues in the tax sector have many obstacles, among others,the level of taxpayer compliance is still low. Many factors that can affect the taxpayercompliance of the individual include taxpayer awareness, tax service and tax sanctions.Objects in this study are individual taxpayers at the Faculty of Engineering SriwijayaUniversity.The purpose of this study is to determine the effect of taxpayer awareness, tax serviceand tax sanctions on Personal Taxpayer compliance in the Faculty of EngineeringSriwijaya University. The type of research used is a type of causal research that isintended to reveal the problems of cause and effect. The sample used in this study is asmany as 188 people taxpayers personally in the Faculty of Engineering SriwijayaUniversity.Based on the results of existing research can be concluded that the consciousness oftaxpayers have a positive but not significant impact on taxpayer compliance in theFaculty of Engineering Sriwijaya University. While for variable of Fiscal service and taxsanction have positive and significant effect to taxpayer compliance. This suggests thatthe higher the tax and tax sanction, the formal taxpayer compliance will be significantlyhigher.